Preparation of the Magnetic Composite Materials Fe3O4/ Hydroxyapatite and Its Application for Removal of 2,4-D and Chrysoidine Crystal - Linh, Han Duy; Anh, Cao Phuong; Viet, Cao; Phong, Le Thi Hong; Hoan, Nguyen Xuan (VNU Journal of Science: Natural Sciences and Technology, 2021)
In this study, magnetite nanoparticles (IONPs), hydroxyapatite (HAp), hybrid composite of magnetite/hydroxyapatite (IONPs-HAp) were prepared by the hydrothermal method. The prepared materials were characterized via Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), vibrating sample magnetometer (VSM), scanning electron microscopy (SEM/EDX), and Zeta phoremeter. The obtained results show that the Fe 3 O 4 have a cubic crystal structure and have a nanoparticle's size (< 100 nm), the nano Fe 3 O 4 were well dispersed with the hydroxyapatite to form the composite IONPs-HAp materials. The adsorption capacity of these materials for 2,4-D (2,4-dichlorophenoxyacetic acid) and Chrysoidine crystal removal were also investigated in the same condition. The prepared IONPs-HAp composite materials have the ability to adsorb selectivity with 2,4-D and Chrysoidine. There results show the potential application of hybrid composite magnetite/hydroxyapatite in the field of environmental treatment.